O impacto do uso do VANT (veículo aéreo não tripulado) no desenvolvimento agrícola - Calabria, Melkzedek (2018)
The technologies that pervade the rural sectors, leverage the development of increasingly effective techniques seeking the best use of the work done by rural producers. Currently the rural environment counts on equipment and vehicles more and more sophisticated, capable of executing complex processes with high precision. Seeking to better understand these agricultural technologies and the results they bring in precision farming, this research aimed to carry out a study focused on one of the most recent technological innovations of the present time: the VANT. Focusing on the impacts brought by this innovation, the author tried to draw a comparison with the traditional and current technologies in the agricultural environment to demonstrate what are the advantages and disadvantages that VANT can offer. To that end the theory of disruptive innovation described by Clayton Christensen was used as a theoretical support of the work, the qualitative method was applied in the research and the method of content analysis was used to treat the information collected in the research field. A rural property was selected in the State of Maranhão as a research field, where an interview was held with its rural producer. Other interviews were made at a scientific research centre focused on agriculture to obtain the source data that could provide the necessary arguments to answer the research question. The data collected included information on the traditional agricultural production processes and equipment currently used as production tools, the costs involved in the processes and for the acquisition of these equipment, the technologies employed, the deadlines for each phase of these processes. These data were used to make a comparison in relation to the results obtained with the use of VANT, which in turn were used for the same purposes as the traditional technologies used in the agricultural area surveyed. The results showed positive and negative points of each technology studied, as well as the advantages and disadvantages when compared to the use of VANT in the same productive processes. Hopefully the results obtained in this research will contribute to the agricultural sector, particularly to rural producers encouraging them to the adoption of this innovation aiming at the improvement of production processes, quality of work and of agricultural production, as well as reduction of time and costs, bringing better results to producers in the industry.